2022
DOI: 10.1111/ddi.13531
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal cline in the foraging dichotomy of loggerhead sea turtles reveals the importance of East China Sea for priority conservation

Abstract: Aim: Quantifying the importance of habitat areas for conservation of highly migratory marine species with complex life histories can be challenging. For example loggerhead turtles (Caretta caretta) nesting in Japan forage both oceanically and neritically after their reproductive period. Here, we aimed to quantify the proportions of turtles using these two contrasting habitats (foraging dichotomy) to suggest priority conservation areas.Location: North Pacific Ocean. Methods:We examined the occurrence of foragin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 83 publications
1
14
1
Order By: Relevance
“…1). She stayed in the East China Sea for 2 years with seasonal migration; she stayed in the northern part of the East China Sea during summer and the southern part during winter [13]. Then, on May 23, 2018, she came back to her initial nesting place at Okinoerabu Island, Japan, for nesting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). She stayed in the East China Sea for 2 years with seasonal migration; she stayed in the northern part of the East China Sea during summer and the southern part during winter [13]. Then, on May 23, 2018, she came back to her initial nesting place at Okinoerabu Island, Japan, for nesting.…”
Section: Resultsmentioning
confidence: 99%
“…We conducted a survey during the main nesting season (from the end of May to the middle of June) from 2015 to 2018. To examine the post-nesting foraging habitat of loggerhead females, satellite relay data loggers (SRDL, Sea Mammal Research Unit, UK) were deployed on eight nesting loggerhead turtles using epoxy putty, two-component epoxy resin, and glass fiber cloth (Konishi Co., Ltd. Osaka, Japan) after nesting [13]. A female turtle (straight carapace length of 91.5 cm) deployed with an SRDL and released at Wanjo Beach on June 27, 2016, was recaptured at the same beach on May 23, 2018.…”
Section: Methodsmentioning
confidence: 99%
“…Both Thoya et al (2022) and Okuyama et al (2022) identified sensitivity of marine vertebrates to stressors like overfishing or bycatch based on physiological and functional (e.g., diet) traits. Thoya et al (2022) used physiological tolerances of billfish species in the Indian Ocean to develop hypotheses for species distribution models, which they then used to relate the distributions of the Indian Ocean billfish community to fishing effort and stock status.…”
Section: Section A: Species Sensitivity/resiliencementioning
confidence: 99%
“…Okuyama et al (2022) used both satellite tracking and stable isotope analysis of diets to characterize within‐population trait variability of loggerhead turtles ( Caretta caretta ) that can inform conservation and management of this species in the north Pacific Ocean. These authors found that loggerhead turtles that nest on beaches in Japan disperse to forage in either the Pacific Ocean (oceanic) or in the east China Sea (neritic) and that these habitat choices are highly associated with differences in traits like diet, body size, and reproductive output.…”
Section: Section A: Species Sensitivity/resiliencementioning
confidence: 99%
See 1 more Smart Citation